Protective mechanisms of tea polyphenols regulating the PI3K/Akt pathway on early brain injury after subarachnoid hemorrhage in rats: Tea polyphenols effects on brain injury via PI3K/Akt pathway - Wu, JiaXun; Zhang, Sunfu (Cellular and Molecular Biology, 2023)
In recent years, numerous studies have demonstrated that tea polyphenols (TPPs) can exert neuroprotective effects through the regulation of the PI3K/Akt pathway. The objective of this work was to verify whether TPPs could protect against early brain injury in rats after subarachnoid hemorrhage (SAH) by modulating the PI3K/Akt pathway. A total of 150 rats were randomly rolled into control (C), TPP, and SAH groups. The TPP and SAH groups underwent endovascular perforation to induce SAH, while C group received only endovascular needle puncture and saline injection. Brain water content, Evans Blue (EB) extravasation assay, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining, Western blot, and RT-PCR analyses were performed. Relative to SAH group, TPP treatment considerably improved neurological function scores following SAH, reduced brain edema, cortical neuronal apoptosis, and blood-brain barrier damage. Levels of aquaporin-4 (AQP4) and apoptosis-related protein Bax were considerably lower in the TPP group than in SAH group. Conversely, levels of anti-apoptotic protein Bcl-2 and tight junction protein Zona occludens 1 (ZO-1) were considerably higher in the TPP group. Furthermore, TPP treatment was found to activate the PI3K/Akt signaling. TPPs can mitigate early brain injury caused by SAH in rats by reducing AQP4 levels, alleviating cortical damage, and attenuating neuronal apoptosis. These findings elucidate the protective mechanisms of TPPs against early brain injury following SAH through the regulation of the PI3K/Akt signaling.